Pelatihan Seni Baca Al-Qur’an Sebagai Upaya Meningkatkan Kemampuan Membaca Al-Qur’an di Desa Matajang - Sulfikar K; Muammanah (INKAMKU : Integrasi Akademisi dan Masyarakat yang Berkualitas, 2025)
The training of the art of reading the Qur’an is one of the efforts to improve the ability to read the Qur’an properly and correctly according to the rules of tajwid. This activity was carried out as part of the Proffesional Real Work Lecture (KKN-P) in Matajang Village, Kahu District, Bone Regency. This program aims to increase children’s interest and skills in the art of reading the Qur’an through the tilawah method. The method used in this study is Participation Action Research, abbreviated as PAR. This method directs researchers to try to connect with the agenda of change in the mindst of society in creating the expected condition through active community participation. The results of the study showed that children exprerienced a significant increase in reading the Qur’an with rhythm, and were more confident in public. In addition, this activity also encouraged community involvement, especially parents, in supporting religious education for their children. With this program, it is hoped that the Qur’an tilawah training can continue to be carried out sustainably to foster a generation of high-achieving Qur’anists